The Analysis Study of Effects of Probiotics, Prebiotics, Lactoferrin and Combination Products for Prevention of Mortality and Morbidity in Preterm Infants: A Comprehensive Systematic Review - Aldila, Raden Rara Farah; Erlich, Willyam Arnando Deggas (International Medical Journal Corp. Ltd, 2024)
Introduction: Preterm infants, particularly those with very low birth weight (VLBW), are at heightened risk for life-threatening complications such as necrotizing enterocolitis (NEC), late-onset sepsis, feeding intolerance, and other gastrointestinal and infectious conditions. In recent years, there has been growing interest in exploring non-pharmacological interventions, such as probiotics, prebiotics, and lactoferrin, to mitigate these risks and improve outcomes in preterm infants. Methods: This systematic review adhered to the PRISMA 2020 guidelines to ensure transparency and consistency. Results: Eight relevant studies were identified and assessed in detail. Findings indicate that probiotic, prebiotic, and lactoferrin interventions have potential benefits in reducing NEC incidence and improving clinical outcomes in VLBW infants. For instance, a study by Chowdhury et al. (2016) found a significantly lower incidence of NEC in the probiotic group (1.9%) compared to the control group (11.5%) with a p-value of 0.044. Additionally, the duration of hospital stay was shorter for the probiotic group, averaging 15.82 days versus 19.57 days for controls (p < 0.001). These results support the use of probiotics in enhancing recovery in VLBW infants. This review highlights the potential of probiotics, prebiotics, and lactoferrin in reducing the incidence of NEC and sepsis, as well as promoting faster achievement of full enteral feeding and shorter hospital stays in VLBW infants. However, the heterogeneity among studies regarding probiotic strains, dosages, and study designs complicates definitive conclusions. Further research is needed to establish standardized treatment protocols and ensure the long-term safety of these interventions in clinical practice.